The Development of the Mathematics Learning Outcome on Equality of Mathayom 2 Students by Using STAD Technique - Khatbanjong, suriyun; Painparadorn, Thanintra (An Online Journal of Education, 2023)
The current research endeavors to develop mathematics learning activities on equality of Mathayom 2 students by using STAD to meet the standard 80/80. Moreover, it aims to compare the mathematics learning outcomes on equality of Mathayom 2 students by using STAD before and after studying. Lastly, its purpose is to study the satisfaction level of Mathayom 2 students on the mathematics learning activities on equality by using STAD. Using random sampling, the sample includes 44 observers, students of an authorized school. Academic year 2022. The research tools include a learning activity plan, tests for Mathematics learning outcomes, and a questionnaire about students’ satisfaction levels. The statistics adopted to analyze the information are the dependent t-test. The research results revealed that the outcome results are considered above standard 85.92/84.77. Next, the comparison of the mathematics learning outcomes before and after studying shows a higher outcome after studying than before, with a statistical significance of .01. Lastly, the overall satisfaction on the mathematics activities is at the highest level with an average of 4.82.